2010
DOI: 10.1074/jbc.m109.081430
|View full text |Cite
|
Sign up to set email alerts
|

Role of HuR and p38MAPK in Ultraviolet B-induced Post-transcriptional Regulation of COX-2 Expression in the Human Keratinocyte Cell Line HaCaT

Abstract: COX-2 (cyclooxygenase-2) is a pivotal player in inflammatory processes, and ultraviolet radiation is a known stimulus for COX-2 expression in skin cells. Here, an induction of COX-2 expression in HaCaT human keratinocytes was observed only upon exposure of cells to UVB (280 -320 nm) but not to UVA radiation (320 -400 nm), as demonstrated by reverse transcription-PCR and Western blotting. Prostaglandin E 2 levels were elevated in cell culture supernatants of HaCaT cells exposed to UVB. COX-2 mRNA stability was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 36 publications
4
46
0
Order By: Relevance
“…Some reports showed that pressure or I/R treatment increased expression of COX-2 (Gomez-Pinilla et al, 2010; Tsutakawa et al, 2009). Additionally, in ultraviolet light B (UVB)-irradiated HaCaT cells COX-2 expression was obviously enhanced (Fernau et al, 2010). In accordance with previous data (Chi and Kim, 2005;Fernau et al, 2010;Tsutakawa et al, 2009), we observed that exposure of HaCaT cells to CoCl 2 upregulated COX-2 expression.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Some reports showed that pressure or I/R treatment increased expression of COX-2 (Gomez-Pinilla et al, 2010; Tsutakawa et al, 2009). Additionally, in ultraviolet light B (UVB)-irradiated HaCaT cells COX-2 expression was obviously enhanced (Fernau et al, 2010). In accordance with previous data (Chi and Kim, 2005;Fernau et al, 2010;Tsutakawa et al, 2009), we observed that exposure of HaCaT cells to CoCl 2 upregulated COX-2 expression.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, in ultraviolet light B (UVB)-irradiated HaCaT cells COX-2 expression was obviously enhanced (Fernau et al, 2010). In accordance with previous data (Chi and Kim, 2005;Fernau et al, 2010;Tsutakawa et al, 2009), we observed that exposure of HaCaT cells to CoCl 2 upregulated COX-2 expression. Furthermore, inhibition of COX-2 by NS-398, a selective inhibitor of COX-2, significantly attenuated CoCl 2 -induced cytotoxicity and secretion of both IL-6 and IL-8, indicating involvement of COX-2 in CoCl 2 -induced cytotoxicity and inflammation in HaCaT cells.…”
Section: Discussionsupporting
confidence: 80%
“…Next, to test whether HuR-depleted cells underwent apoptosis during CoCl 2 treatment, we quantified the percentage of annexin V/propidium iodide-positive cells using flow cytometry. As shown in It has previously been shown that HuR is exported to the cytoplasm under conditions of stress such as UV treatment (36), serum starvation (37), heat shock (34), and staurosporine administration (15). We, therefore, speculated that CoCl 2 treatment, mimicking hypoxic stress, would influence HuR translocation.…”
Section: Oral Cancer Tissues Exhibit Cleavage Of Hur-it Is Wellmentioning
confidence: 99%
“…This observation clearly indicates that HuR is exported from the nucleus in IR-treated cells and could be involved in post-transcriptional regulation. Previously, it has been shown that ultraviolet light (35) and other stresses (34) induce HuR translocation from nucleus to cytoplasm. Herein, we show that in vivo, HuR is exported to the cytoplasm in IR-induced oral mucositis.…”
Section: Hur Undergoes Cleavage Modifications In Experimental Oralmentioning
confidence: 99%